Endovascular Management of Spontaneous Bilateral Symptomatic Vertebral Artery Dissections - Cohen, José E.; Gomori, John Moshe; Umansky, Felix (American Journal of Neuroradiology, 2003)
Summary: Extracranial vertebral artery (VA) dissection may lead to significant arterial stenosis, occlusion, or pseudoaneurysm formation with subsequent hemodynamic and embolic infarcts. To prevent thromboembolic complications, anticoagulation with intravenous heparin followed by oral warfarin has been recommended for all patients with acute dissections, regardless of the type of symptoms. Nevertheless, anticoagulation is not innocuous and may be associated with hemorrhagic transformation of a cerebral infarction or may be ineffective to prevent symptoms or dissection progression. We present a case of a bilateral spontaneous extracranial VA dissection presenting with multiple embolic infarctions. The dominant VA was reconstructed with multiple in-tandem stents and the contralateral VA, proved to be the source of emboli, was occluded with coils. Stent-assisted VA angioplasty has rarely been reported in the management of spontaneous dissections and appears to be a safe, effective and immediate method of restoring vessel lumen integrity and should be considered in the therapy of selected cases of VA dissection.